Model based computation of electromagnetic forces in magnetic confinement toroidal devices by using magnetic measurements. (1st June 2021) - Abate, D; Marchiori, G; Berton, G; Bonotto, M; Cordaro, L; Grando, L; Bettini, P
Abstract: In this paper we present a method to compute spatial and time evolution of electromagnetic forces in magnetic confinement fusion devices based on a combination of signal analysis of magnetic measurements with a simple electromagnetic modelling. The method allows analyzing the whole plasma discharge including fast transient phenomena such as fast terminations or disruptions. It has been tested and verified on RFX-mod, an experiment equipped with a non-continuous toroidal passive stabilizing shell, but it can be applied to cases with continuous wall such as tokamak devices, as well. An experimental plasma discharge, with a fast termination phenomenon at the end of the flat-top phase, has been analyzed and the related forces have been computed by using two different sets of data: synthetic magnetic field measurements provided by ANSYS simulation and real experimental ones. The results are in good agreement in all the phases of the plasma discharge. Moreover, because of the very low-computational requirements, it is shown that the presented method can be used as a tool for real-time monitoring of the electromagnetic forces on the shell to be integrated in the protection system of the future RFX-mod2 experiment.